Existence, uniqueness, and asymptotic stability for a thermoelastic plate - Amendola, G. (Нелінійні коливання, 2003)
In this note we are concerned with the linear theory of a thermoelastic plate when a rate-type equation is assumed for the heat flux. We consider an initial boundary-value problem for this plate and show the existence, uniqueness, and asymptotic stability of the solution. Thermodynamic restrictions on the assumed constitutive equations are also derived. Finally, we give the expression of a pseudo free energy.